Developing Teaching Guidelines and Learning Module of Speaking for General Communication: Students’ Perception and Needs - Suryani, Lilis; Apriliyanti, Dewi Listia; Rohmat, Fauziah Nur (LPPM Universitas Advent Indonesia, 2021)
Covid-19 is still spreading all over the world, including Indonesia and it has a big impact on the education sector. Online learning is a way to reduce the spread of the covid-19 outbreak. Educators and students, whether ready or not, have to do online learning because to avoid the spread of this pandemic. Therefore, this research would like to know students’ perception and needs toward speaking for general communication. This study is conducted using a survey method based on Kirkpatricks’ Model. The survey accumulated and investigated learners' perception of speaking for general communication course after they learned and practiced it in the online lecturing class. The respondents of the survey were selected using the purposive sampling method. the subject of this study was 165 students of a first semester, the English Language Study Program at IKIP Siliwangi Bandung, who was taking a speaking for a general communication course. Based on the result, most of the students had positive perceptions and they could improve their speaking skills after the teaching session. In fact, there are three things that are not really appropriate with the students’ needs, they are handout/teaching materials, technological confidence, and topics of materials. Therefore, further research is needed to develop the module/handout based on students’ needs.